Adventure Destinations In Indonesia: The Function Of Perceived Value, And Effect On Visitor Experience And Revisit Intention - Mahmudi Rosid, Moch. (International Journal of Educational Research & Social Sciences, 2023)
Management of the Mt. Penanggungan destination which has not been managed well. Can management science contribute to the Mt. Penanggungan adventure tourism destination? This research examines marketing management in adventure tourism destinations, which is usually synonymous with customer loyalty, and the determinant is always "satisfaction" but here we try another variable, namely "perceived value", then its influence on visitor experience and revisit intention. The aim of this research is to determine the role of perceived value in adventure destinations in Indonesia, and how much visitor experience influences it and then its influence on revisit intention. The sample used 233 visitors to Mt. Penanggungan who climbed at least once according to Hair et al., infinite population, using the Convenience Sampling technique as part of a non-probability sampling design. The method uses a quantitative approach with descriptive research according to Creswell, and explanatory according to Neuman. Statistical analysis uses Path Analysis, previously testing the data: validity test and reliability test. Analyzed using descriptive analysis. Tested using classic assumption tests: normality test, multicollinearity test, heteroscedasticity test, autocorrelation test. Hypothesis tests were carried out: t test, F test, and R² test. And finally analyzed using path analysis. The results of this research hypothesis test: visitor experience influences revisit intention, visitor experience influences perceived value, perceived value influences revisit intention, visitor experience and perceived value influence revisit intention. Managers are advised to maintain the stability of the influence of each variable, Visitor Experience to Perceived Value, Visitor Experience to Revisit Intention, Perceived Value to Revisit Intention, so that all paths are consistently positive and significant on an ongoing basis, and ultimately increase the number of return visits to Mt. Penanggungan, indirectly improving the economy of residents around the slopes of Mt. Penanggungan, especially residents of Tamiajeng Village on the south side, residents of Seloliman Village on the west side, residents of Wonosunyo Village on the east side, and residents of Watonmasjedong Village on the north side.